2021
DOI: 10.1002/fsn3.2181
|View full text |Cite
|
Sign up to set email alerts
|

Grain quality evaluation of japonica rice effected by cultivars, environment, and their interactions based on appearance and processing characteristics

Abstract: Appearance and processing characteristics of 45 japonica rice samples, collected from different regions in Jiangsu province, were investigated and evaluated in this study. Specifically, the chalkiness degree had been presented significant differences among different cultivars and regions. The average chalkiness degree varied from 6.81% to 15.34% for different regions and from 1.93% to 28.31% for different cultivars. The minimum head rice rate of cultivars from four regions, NJ9108 (HA), was 80.5%. The AC of CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…It was reported that major QTL clusters closing to Wx and ALK locus could be detected in different environments, and these QTL clusters could affect eating and cooking quality [ 18 ]. In this study, it showed that AC, PC, GC, ASV and RVA profiles were affected by genotypes, which was similar to previous studies [ 15 , 17 ]. AC ranged from 9.0 to 19.1%, belonging to low and medium amylose, and japonica rice had wider genetic diversity ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was reported that major QTL clusters closing to Wx and ALK locus could be detected in different environments, and these QTL clusters could affect eating and cooking quality [ 18 ]. In this study, it showed that AC, PC, GC, ASV and RVA profiles were affected by genotypes, which was similar to previous studies [ 15 , 17 ]. AC ranged from 9.0 to 19.1%, belonging to low and medium amylose, and japonica rice had wider genetic diversity ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Genotype, environment and their interaction could influence rice starch properties. It is reported that rice starch and its properties are controlled by different alleles of major genes or QTLs [ 13 , 14 , 15 ], and they also vary in different climates and locations and in different seasons and years [ 16 , 17 , 18 ]. It is well-known that rice sensory quality is controlled by many genes concentrated in the synthesis of rice starch and protein and influenced by the physicochemical properties of starch [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starch viscosity was measured using a rapid viscosity analyzer (RVA‐3, Newport Scientific, Warriewood, NSW, Australia) and analyzed using companion software Thermal Cycle Windows (TWCs). The specific operation steps are described by Xia et al 18 . RVA spectrum eigenvalues included peak viscosity, hot paste viscosity, cool paste viscosity, breakdown viscosity obtained from the peak viscosity minus hot paste viscosity, setback viscosity obtained from cool paste viscosity minus hot peak viscosity, consistency viscosity obtained from cool viscosity minus hot paste viscosity, peak time and pasting temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Rice grains were equilibrated for 3 months after harvest, and empty grains were removed. The brown rice, milled rice and head-milled rice rates were measured as described by Xia et al 18 Grain chalkiness, chalky rice rate and length-width ratio were determined using an appearance quality scanner (MICROTEK, ScanMaker i800 plus). The amylose content was determined according to the method of Zeng et al 19 Gel consistency was determined according to the method of Huang et al 20…”
Section: Grain Quality Analysismentioning
confidence: 99%
“…High temperature during the rice grain-filling stage often results in lower quantity and worse quality, such as higher chalkiness and lower grain-setting rate [19]. Grain chalkiness affects the appearance of rice.…”
Section: The Oslea1b Mutants Showed Greater Sensitivity To High Tempe...mentioning
confidence: 99%